Assessment of Agricultural Mechanization's Influence on WIP Costs at PT. Great Giant Pineapple PG4 Lampung Timur - BAKHRI, SYAIFUL; Sulastri, Susi; Sandora, Putri; Gunawan, Gunawan (Journal of Research in Social Science and Humanities, 2024)
The advancement of the times, marked by progress in science and technology, has had a profound impact on human life. As thinking beings, humans continuously strive to develop various aspects of life to improve their quality of living. This process of change is ongoing, especially in the agricultural sector, which plays a crucial role in human life, and in industries such as PT. Great Giant Pineapple, one of the largest fruit plantation companies in Indonesia that has exported its pineapple products to nearly every corner of the world. The objective of this study is to determine and analyze the differences in Work In Progress (WIP) costs before and after the implementation of mechanization in the Banana Department at PT. Great Giant Pineapple PG4. The data used in this study are quantitative, and the methods for data collection include documentation and interviews. For data analysis, a two-sample independent t-test was employed. The results of the data analysis show that the Sig. (2-tailed) value from the Independent Samples Test table is 0.014, which is less than 0.05. Based on the decision criteria for the t-test, it can be concluded that Ha is accepted and Ho is rejected, indicating that there is a significant difference in WIP costs before and after the implementation of mechanization at PT. Great Giant Pineapple PG4 Banana Department. Prior to mechanization, there was an overcost of IDR 1,674,000,000, which was reduced to IDR 749,998,500 after mechanization, resulting in a total saving of IDR 924,001,500. This reduction is attributed to the shift from using 12 manual laborers to just 1 laborer operating a machine, which cut down the workforce by 11 people and simultaneously increased productivity and quality, processing land from 1 hectare to 7 hectares.